Study of Multivariate Background Error Characteristics of Convective System on Plateau Slope and Typhoon System Based on Convective-Scale Ensemble Samples - Wanli ZHANG; Yuanbing WANG; Rou LI; Yaodeng CHEN; Deming MENG; Xinyao QIAN; Xili JIN (Gaoyuan qixiang, 2025)
The effective assimilation of observation data in the slope areas of the Qinghai-Xizang （Tibetan） Plateau and typhoon systems has a significant impact on the capabilities of weather forecasting in China， with background error being a key factor affecting the performance of data assimilation.The purpose of this study is to gain a deeper understanding of the characteristics of background errors in conventional control variables and hydrometeor control variables within convective systems on the slopes of the Qinghai-Xizang （Tibetan） Plateau and typhoon systems， so as to develop the data assimilation scheme which is applicable to the convective systems on the slopes of the Qinghai-Xizang （Tibetan） Plateau and typhoon systems.This study employs the Ensemble Transform Kalman Filter （ETKF） and the hybrid Ensemble-Variational data assimilation method to update the ensemble perturbation and the ensemble mean respectively to produce convective-scale ensemble forecast samples with 80 ensemble members and 4-kilometers resolution.This study focuses on cases of convective weather from the northeast slope of the Qinghai-Xizang （Tibetan） Plateau in mid-August 2022 and Typhoon "Meihua"， the 12th typhoon of 2022.Multivariate background error covariances， including those for multiphase hydrometeor and vertical velocity， were computed through physical transformation， vertical transformation， and horizontal transformation.Analyses of the spatial error characteristics， including the eigenvalues， eigenvectors， and characteristic length scales were conducted， and the results of the analyses indicate that background errors are more pronounced in the case of convective system on the slope of the Qinghai-Xizang （Tibetan） Plateau in comparison to the typhoon system.At the same time， the simulation of hydrometeor variables and vertical velocity is less precise in the case of convective system on the slope of the Qinghai-Xizang （Tibetan） Plateau compared to the typhoon system.In the context of data assimilation for these comparable convective systems， the analysis tends to be more aligned with observations and less so with the background， this feature highlights the necessity for high-quality and comprehensive observations in the slope areas of the Qinghai-Xizang （Tibetan） Plateau.In addition， the atmospheric characteristics and the horizontal scale of hydrometeor variables and vertical velocity in the case of convective system on the slope of the Qinghai-Xizang （Tibetan） Plateau display smaller and more localized features compared with those observed in the typhoon system.Moreover， hydrometeor control variables and the vertical velocity exhibit smaller horizontal scales and more pronounced localized characteristics compared to conventional control variables， therefore potentially leading to the influence range of observations and information related to hydrometeor control variables in the slope areas of the Qinghai-Xizang （Tibetan） Plateau relatively limited in the context of the subsequent assimilation analysis.